Latar Belakang Pendidikan Orang Tua dan Pola Asuh Keluarga Berpengaruh Terhadap Perkembangan Moral Spiritual Anak - Miftahudin Miftahudin (Program Studi Pendidikan Agama Islam (PAI) Sekolah Tinggi Agama Islam Al Azhar, 2021)
Parents’ educational background and family parenting affected on the development of children spiritual moral. The level of education possessed by parents was one of the factors that influenced parenting provided by parents to children which in turn will affect the development of child’s spiritual moral, but that we need to know is the extent to which the role of these factors could influenced their spiritual moral development. Based on the research statement,the aimed of this research was to know the significant of parents’ educational background and family parenting on the development of children spiritual moral in Islamic Junior High School of Al-khairiyah Pabuaran-Cilegon. This research used a survey method with a quantitative approach. From the result of the research known that parents’ educational background effected on the development of children spiritual moral shown that tcount > ttable (5.030 > 2.0280), and family parenting affected on the development of children spiritual moral it’s shown that tcount > ttable (14.743 > 2.0280), and between X1 and X2 variable appeared that r count was 0,51 all of which were greater than r table 0,329, so it concluded that there was a significance influence of parents’ educational background and familyparenting on the development of children spiritual moral.